The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18203/2349-3933.ijam20191165
|View full text |Cite
|
Sign up to set email alerts
|

Study of expression of PTEN and Cyclin D1 in endometrium at a tertiary care centre

Abstract: Background: To study the expression of PTEN (Phosphatase and Tensin homologue) and Cyclin D1 in normal, hyperplastic and neoplastic endometrium by immunohistochemistry and to corroborate the interrelationship between PTEN and Cyclin D1 in normal to neoplastic endometrial disorders including endometrial carcinoma.Methods: Formalin fixed paraffin embedded (FFPE) sections of spectrum of endometrium in fifty different cases were taken from secretory phase to endometrial carcinoma and subjected to Immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 20 publications
(22 reference statements)
3
8
2
Order By: Relevance
“…PTEN positivity was found in all 47 (100%) cases of proliferative endometrium, 18 (90%) cases in secretory endometrium, which was similar to several studies in which PTEN positivity was seen in 100% of the cases of proliferative and secretory endometrium. 10,12,13,14,15,16 However , in the study done by Tantbirojn et al 17 , 100% positivity was seen in proliferative endometrium but only 60% in secretory endometrium.…”
Section: Resultsmentioning
confidence: 98%
“…PTEN positivity was found in all 47 (100%) cases of proliferative endometrium, 18 (90%) cases in secretory endometrium, which was similar to several studies in which PTEN positivity was seen in 100% of the cases of proliferative and secretory endometrium. 10,12,13,14,15,16 However , in the study done by Tantbirojn et al 17 , 100% positivity was seen in proliferative endometrium but only 60% in secretory endometrium.…”
Section: Resultsmentioning
confidence: 98%
“…Yan et al [25] demonstrated that [42.3%] of their cases exhibited positive expression of Cyclin D1. While Suri et al [32] & Thukral et al [4] detected that [85.71%] of carcinoma endometrium were positive for Cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer is the most common malignancy of the female genital system. Endometrial carcinoma development involves the stepwise acquisition of several genetic alterations involving oncogenes and tumor suppressor genes [4] . Various prognostic factors have been widely researched to improve the patients' management, treatment, and follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations